Mechanical properties of biopolymer-stabilised soil-based construction materials. Issue 4 (16th November 2017) - Muguda, S.; Booth, S. J.; Hughes, P. N.; Augarde, C. E.; Perlot, C.; Bruno, A. W.; Gallipoli, D.
Abstract : Soil-based construction materials are of interest as structural building materials due to their green credentials, as well as being present in many historical structures. For effective conservation of the latter, and to motivate greater uptake for new construction, understanding of the mechanical and hydraulic properties of these materials is in need of improvement. Earthen construction materials can be considered to be manufactured unsaturated soils, and advances in understanding can be made by considering them from a geotechnical point of view. This paper presents initial results from a major programme of testing, seeking improved properties for earthen construction materials, where unusual organic compounds have been employed as stabilisers. Two gums (guar and xanthan) used as stabilisers for a soil mixture are shown to have significant effects on certain mechanical properties, some of which can be explained, and other aspects which are in need of further investigation.